PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA TEMA 8 PERISTIWA ALAM SUB TEMA 4 BENCANA ALAM KELAS 1 - Cornelia Cempaka Dewi; Efa Fadhilah; Yulita Dwi Lestari (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
The purpose of this research is to develop multimedia products as alternative media in learning in elementary schools. This study uses a method of research and development or Research and Development (R&D) Borg and Gall. The results of this research are learning videos for class 1 Theme 8 Natural Events Sub Theme 4 Natural Disasters. The conclusions of this study are 1). Teachers must understand and be able to take advantage of existing technology so that they can develop multimedia to support the learning process to meet learning objectives, 2). Multimedia development can be used as a solution for teachers in conveying information/material because multimedia can help students understand abstract concepts or material, and 3). For the quality of developing education, multimedia development is important for learning by every educator and prospective educator.